COMPARISON OF TWO INTRACANAL MEDICAMENTS IN RESOLUTION OF APICAL RADIOLUCENCY - Riaz, Amna; Maxood, Anser; Abdullah, Saeeda; Saba, Kiran; Din, Shahab Ud; Zahid, Shahreen (Journal of Ayub Medical College Abbottabad, 2018)
ABSTRACT: Introduction: Calcium hydroxide has been used as an intracanal medicament as gold standard against root canal pathogens but its combination with chlorhexidine is not being employed in routine despite its documented efficacy and results. Objective: The objective of this randomized controlled clinical trial was to compare radiographic evidence of periapical healing after root canal treatment with an interim calcium hydroxide and calcium hydroxide with 2% chlorhexidine dressing. Materials & Methods: A total of 60 patients of either gender were included in the study.The age range was 15-60 years with the radiographic evidence of radiolucency of 2-4 mm in size. Both maxillary and mandibular teeth till 1st molars were selected. Teeth with previous endodontic treatment, mentally handicapped and terminally ill patients were excluded. Selected patients were placed randomly into Group I (calcium hydroxide alone) and in Group II (calcium hydroxide in combination with 2% chlorhexidine gel). Obturation and permanent filling was done at 14th day. The patient was recalled after 90 days of obturation and a radiograph was taken. Final outcome was measured at the end of 90thday of obturation. Results: The mean healing time in terms of percentage change in size of apical radiolucency at 3 months was 91.03% for group I and 97.26% for group II with p value 0.13 (not significant).The results suggested comparable outcome after medication with 2%chlorhexidine with calcium hydroxide but 2% chlorhexidine still showed better results than the group without CHX in terms of percentage healing time. Conclusion: This study concluded that calcium hydroxide in combination with 2% chlorhexidene as intracanal medicament results in better resolution of periapical radiolucency in terms of percentage change. Background: As a gold standard, calcium hydroxide has always been used as a root canal medicament against root canal pathogens but its combination with chlorhexidine is not being employed in routine despite its documented efficacy and results. The objective of the study is to compare calcium hydroxide and combination of calcium hydroxide with 2% CHX on the basis of radiographic evidence of resolution of periapical radiolucency when they are used as an interappointment dressing /intracanal medicament for 14 days. Method: A total of 60 patients of either gender was included in the study. The age range was 15-60 years with the radiographic evidence of radiolucency of 2-4 mm in size. Both maxillary and mandibular teeth till first molar were selected. Teeth with previous endodontic treatment mentally handicapped and terminally ill patients were excluded. Selected patients were placed randomly into Group 1 (calcium hydroxide alone) and in Group 2 (calcium hydroxide in combination with 2% chlorhexidine gel). Obturation and permanent filling was done at 14th day. The patient was recalled after 90 days of obturation and a radiograph was taken. Final outcome was measured at the end of 90thday of obturation. Results: The mean of percentage reduction in size of apical radiolucency at 3 months was 91.03% for group 1 and 97.26% for group 2 with p-value 0.13 (not significant). The results suggested equivalent results after medication with 2%chlorhexidine with calcium hydroxide but 2% chlorhexidine still showed better results than the group without CHX in terms of healing. Conclusion: This study concluded that calcium hydroxide in combination with 2% chlorhexidene as intracanal medicament results in better resolution of periapical radiolucency in terms of percentage resolution of periapical radiolucency. Keywords: Root canal treatment; calcium hydroxide; chlorhexidine